Numerical prediction of elastic properties for alumina green parts printed by stereolithography process. Issue 3 (March 2021) - Michaud, P.; Pateloup, V.; Tarabeux, J.; Alzina, A.; André, D.; Chartier, T.
Abstract: Stereolithography is a process based on the photopolymerization of a UV-reactive system consisting of ceramic particles dispersion in a curable resin. A key issue of this process is the control of the rigidity of green parts, which are strongly related to UV light exposure. This work is focused on the numerical prediction of green part stiffness according to stereolithography manufacturing parameters. A first macroscopic approach, based on the modelling of ceramic suspension polymerization, makes it possible to establish a relationship between the exposure and the Young's modulus. A second microscopic approach, using a periodic homogenization technique based on the strain energy, is applied to a 2D finite element model to evaluate the effective elastic properties. Numerical results show that macroscopic model is able to provide a Young's modulus with a good level of accuracy. The modelling results from the microscopic model demonstrate an acceptable convergence with the experimental Young's modulus.